Beyond Words: Indigenous Hospitality and Linguistic Landscaping in NTT Food Truck Entrepreneurship - Saragi, Rulli; Malelak, Merlyn Luisa; Milyardo, Boiris; Laka, Egidius Pai (Politeknik Negeri Bandung, 2026)
This study examines the operationalization of translingual repertoires and the indigenous teknok ta’ek hospitality philosophy as mechanisms for competitive differentiation in the food truck sector at Lasiana Beach, Kupang. Utilizing a multisited ethnographic design over an eight-week period, the researchers gathered data through participatory observations and semi-structured interviews with 15 key stakeholders, including tourism officials, business owners, and suppliers. Data analysis followed the Miles, Huberman, and Saldaña (2014) framework, ensuring methodological rigor through source triangulation. Findings indicate that the systematic integration of regional vocabulary—such as Dawan, Tetun, and Rote—into menu naming increases customer interaction duration by 35% and purchase conversion by 20%. Furthermore, the institutionalization of teknok ta’ek values through Ama/Ina kinship protocols transforms transactional service into relational exchange, significantly enhancing brand loyalty and yielding an average revenue increase of 30%. The study introduces the concept of